2014
DOI: 10.1080/00071005.2014.980222
|View full text |Cite
|
Sign up to set email alerts
|

Emotion as a Student Resource in Higher Education

Abstract: This article offers a critical examination of students' emotional bargaining in higher education. Based on an analysis of student emails and staff interviews, the article uses a case-study approach to explore the nature of this behaviour and the motivational drivers behind it. The paper reveals an amalgam of socio-cultural and educational factors, identifying the particular importance of a neo-liberally inflected climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In contrast, some Australian teacher educators stressed their effort not to display strong negative emotions in order to maintain positive relationships with students and not to risk authority. In a recent study, Bartram (2015) found that sometimes students take advantage of close and caring relationships with HE teachers, a behavior he coined "affective strategizing" (p. 68). This suggests that a caring attitude of HE teachers may not necessarily be positive, as it comes with individual costs for the teacher (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some Australian teacher educators stressed their effort not to display strong negative emotions in order to maintain positive relationships with students and not to risk authority. In a recent study, Bartram (2015) found that sometimes students take advantage of close and caring relationships with HE teachers, a behavior he coined "affective strategizing" (p. 68). This suggests that a caring attitude of HE teachers may not necessarily be positive, as it comes with individual costs for the teacher (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Colleagues at each institution distributed information about the study via staff networks. In the end, 43 participants volunteered to complete anonymous on-line questionnaires, consisting of 16 closed and open-ended items structured around Bartram's (2015) analytical framework (more detail is provided in the findings section below). Questions consisted of several typessome capturing categorical detail, while others were based on a mixture of agreement/item selection/open commentary on various aspects of students' emotional bargaining.…”
Section: Research Context and Designmentioning
confidence: 99%
“…Swedish and 6 Dutch, the others mostly expressing uncertainty. As for the 'emotional scenarios' underpinning the students' AS-behaviours, table 2 presents the numbers of staff agreeing with the contexts identified by Bartram (2015)…”
Section: Contextsmentioning
confidence: 99%
See 2 more Smart Citations